α-Dystroglycan Is a Laminin Receptor Involved in Extracellular Matrix Assembly on Myotubes and Muscle Cell Viability - Montanaro, Federica (The Rockefeller University Press, 1999)
α-Dystroglycan (α-DG) is a laminin-binding protein and member of a glycoprotein complex associated with dystrophin that has been implicated in the etiology of several muscular dystrophies. To study the function of DG, C2 myoblasts were transfected stably with an antisense DG expression construct. Myotubes from two resulting clones (11F and 11E) had at least a 40–50% and 80–90% reduction, respectively, in α-DG but normal or near normal levels of α-sarcoglycan, integrin β1 subunit, acetylcholine receptors (AChRs), and muscle-specific kinase (MuSK) when compared with parental C2 cells or three clones (11A, 9B, and 10C) which went through the same transfection and selection procedures but expressed normal levels of α-DG. Antisense DG-expressing myoblasts proliferate at the same rate as parental C2 cells and differentiate into myotubes, however, a gradual loss of cells was observed in these cultures. This loss correlates with increased apoptosis as indicated by greater numbers of nuclei with condensed chromatin and more nuclei labeled by the TUNEL method. Moreover, there was no sign of increased membrane permeability to Trypan blue as would be expected with necrosis. Unlike parental C2 myotubes, 11F and 11E myotubes had very little laminin (LN) on their surfaces; LN instead tended to accumulate on the substratum between myotubes. Exogenous LN bound to C2 myotubes and was redistributed into plaques along with α-DG on their surfaces but far fewer LN/α-DG plaques were seen after LN addition to 11F or 11E myotubes. These results suggest that α-DG is a functional LN receptor in situ which is required for deposition of LN on the cell and, further, implicate α-DG in the maintenance of myotube viability.